2019
DOI: 10.1007/s12182-019-0321-y
|View full text |Cite
|
Sign up to set email alerts
|

Asphaltene aggregation studied by molecular dynamics simulations: role of the molecular architecture and solvents on the supramolecular or colloidal behavior

Abstract: Asphaltene aggregation is a subject under vivid discussion: There are several parameters one needs to determine before its behavior can be mastered and better target solutions can be tailored. The nature of asphaltene aggregation (colloidal or supramolecular) and the role of solvents and their mixtures are among the least understood parameters in asphaltene science. This paper addresses molecular dynamic simulations to correlate the aggregation properties of asphaltenes, their molecular structure and the conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 44 publications
5
33
0
Order By: Relevance
“…Molecular simulation methods provide an efficient way to explore the role of metalloporphyrins in asphaltene aggregation at the atomic scale. The investigation of asphaltene aggregation via a molecular simulation route should consider both the thermodynamic conditions [210,211] and chemical compositions [210,212,213] of the system. The competition between π-stacking interactions due to the aromaticity and the formation of hydrogen bonds due to the presence of heteroatoms demonstrated that the presence of hydrogen bonds is a key factor for the formation of large aggregates [213].…”
Section: Role Of Heteroatoms and Metals In Asphaltene Aggregationmentioning
confidence: 99%
“…Molecular simulation methods provide an efficient way to explore the role of metalloporphyrins in asphaltene aggregation at the atomic scale. The investigation of asphaltene aggregation via a molecular simulation route should consider both the thermodynamic conditions [210,211] and chemical compositions [210,212,213] of the system. The competition between π-stacking interactions due to the aromaticity and the formation of hydrogen bonds due to the presence of heteroatoms demonstrated that the presence of hydrogen bonds is a key factor for the formation of large aggregates [213].…”
Section: Role Of Heteroatoms and Metals In Asphaltene Aggregationmentioning
confidence: 99%
“…At higher concentrations, these aggregates form clusters, which have smaller binding energies than the ones occurring within the nanoaggregates. Molecular dynamics simulations (MD) and dissipative particle dynamics (DPD) are consistent with the presence of nanoaggregates, in bulk, and at liquid/liquid interfaces. , …”
Section: Introductionmentioning
confidence: 74%
“…The result can be a rather stable structure, as it is for example reported for the benzene dimer (dissociation energy (moderate hydrogen bonds: [ 29 ], van der Waals bonds: ) ) [ 30 , 31 ], though the importance of -stacking, that means the face-centered stacking arrangement of aromatic molecules, for aromatic–aromatic interactions is still under discussion [ 32 ]. Nevertheless, - interactions are considered as an important interaction among others responsible for asphaltene aggregation and precipitation [ 33 , 34 , 35 , 36 ]. Recently, an unusual type of parallel -stacking, the so-called pancake bonding, which occurs between radicals with highly delocalized electrons, as they occur in asphaltenes, gained attention with regard to the aggregation of asphaltenes [ 37 ].…”
Section: Theorymentioning
confidence: 99%